2022
DOI: 10.3390/horticulturae8030202
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Culture of Eremurus spectabilis (Liliaceae), a Rare Ornamental and Medicinal Plant, through Root Explants

Abstract: Eremurus spectabilis M. Bieb, a perennial herbaceous wild species, is commonly used in the horticultural, ornamental, and pharmaceutical markets. Studies on the tissue culture systems for this species would be beneficial for mass multiplication as well as for future breeding programs. An in vitro propagation technique was established here using tuberous root explants as unique and responsive starting materials for culture initiation. The proliferated calli were sub-cultured on shoot proliferation media and reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…The effect of auxin NAA for better rooting was also shown in various studies, such as in Sapindus trifoliathus (Asthana et al, 2011) and A. africana (Okello et al, 2021). Unlike our study, the half-strength MS medium supplemented with IBA was found to be the optimal root growth medium in Rhododendron wattii (Mao et al, 2018), H. populifolia (Upadhyay et al, 2020), Trichilia pallida (de Souza Prim et al, 2021), and Eremurus spectabilis (Basiri et al, 2022).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The effect of auxin NAA for better rooting was also shown in various studies, such as in Sapindus trifoliathus (Asthana et al, 2011) and A. africana (Okello et al, 2021). Unlike our study, the half-strength MS medium supplemented with IBA was found to be the optimal root growth medium in Rhododendron wattii (Mao et al, 2018), H. populifolia (Upadhyay et al, 2020), Trichilia pallida (de Souza Prim et al, 2021), and Eremurus spectabilis (Basiri et al, 2022).…”
Section: Discussionsupporting
confidence: 72%
“…In our study, half-strength MS medium alone or in combination with the three auxins, viz ., IAA, IBA, and NAA, was chosen for rhizogenesis. The requirement of a half-strength MS medium for root induction has been reported in several plant species, such as Eremurus spectabilis (Basiri et al, 2022 ) and Artemisia arborescens (Riahi et al, 2022 ). However, in contrast to our study, a full-strength MS medium supplemented with auxin was found suitable for root induction in the microshoots in A. africana (Okello et al, 2021 ) and D. anosmum (Nguyen et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The substrate actually has to be permeable, and well-drained. Additionally, it ought to make it easier to obtain water and nutrients, and for gas exchange (Basiri et al, 2022). The aforementioned will encourage plant survival, growth, and the establishment of a strong root and shootorganisation.…”
Section: Discussionmentioning
confidence: 99%
“…Observation of callus growth was carried out visually, including the number of explants that formed callus, the structure or type of callus formed, the color, size, and areas that formed callus more quickly, carried out once every 1 week for up to 8 weeks. The color of the callus formed was observed also [15]. The stages of callus development are scored using a scale of 0-4, namely 0: no callus development, 1: small callus development, 2: moderate callus development, 3: large callus development, and 4: very large callus development [16].…”
Section: Research Locationmentioning
confidence: 99%